Gut microbiota may contribute to the postnatal male reproductive abnormalities induced by prenatal dibutyl phthalate exposure. (January 2022) - Zhang, Tongtong; Zhou, Xiang; Zhang, Xu; Ren, Xiaohan; Wu, Jiajin; Wang, Zhongyuan; Wang, Shangqian; Wang, Zengjun
Abstract: Phthalate is an environmental endocrine disruptor that causes direct and intergenerational male reproductive damage. However, its mechanisms require further investigation. The role of gut microbiota in male reproductive function has been gradually revealed in the past. To explore the intergenerational testicular injury and the influence on offspring gut microbiota of the widely used phthalate dibutyl phthalate (DBP), we conducted a prenatal DBP exposure experiment with microbiota sequencing. We finally explained the gestational DBP exposure-induced gut dysbacteriosis, which is one of the mechanisms of testicular injury in the offspring. The occurrence of seminiferous atrophy and spermatogenic cells apoptosis showed a slight increase. Our study partially supported the results of previous research works on the characteristics of gut dysbacteriosis, which featured the increased relative abundance of Bacteroidetes, Prevotella and P. copri . Focusing on the role of gut microbiota in reproductive function is important. Future studies need to investigate the relationship between environmental pollution and human health. Graphical abstract: Image 1 Highlights: Gestational DBP exposure induced serious testicular injuries in the offspring. Gut dysbacteriosis of the offspring exposed maternally to DBP were observed. Dysbacteriosis featured an increase of bacteria negatively related to sperm function. Dysbacteriosis induced by DBP exerted a mild male reproductive damage effect.